Ketertarikan Siswa terhadap Bahan Bacaan - Rachman, Yeni Budi; Rachman, Margareta Aulia; Rachmawati, Yuliana Mukti (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2018)
This study identifies the students’ reading interest of Sekolah Dasar Negeri 1 Depok Baru, West Java. This research uses a quantitative research approach with descriptive method. The data was collected by using survey. The results showed that students have their own reading interest. Their favorite genre of reading materials includes religious stories, comic, and short novels. The findings suggest that parents need to introduce another reading material variation such as newspapers. Parents are also encouraged to supervise their children while reading comic.